THE POWER OF AMIRI BARAKA’S POLITICAL THOUGHTS TO THE AFRICAN-AMERICAN MOVEMENT IN AMERICA - Irma Febriyanti (Universitas Gadjah Mada, 2015)
Imamu Amiri Baraka is an artist, activist, and also an African-American leader who was born in Newark, New Jersey. Throughout his prolific career in American literature, he was able to generate some important political issues in defending the Black Power which was a perpetuating challenge for African-American intellectuals in the 1960s-1970s.This research is written under American Studies discipline, which takes politics to gain an African-American politics’ point of view, sociology to explore the theory of race and social conflict in the United States, and cultural studies to understand the struggle of African-Americans towards white Americans.The findings of this research show Baraka’s adeptness in his dual role as artist and politician through his political thoughts which has a never-ending development of his political consciousness. Baraka’s intellectual and political thought formation has moved through verydistinct stages and they are: Black Cultural Nationalism, Black Solidarity and Black Marxism. His final political stage has a broader consciousness that reveals capitalism in the Western world and this revelation of capitalism declared its theme of death and despair, moral and social corruption with its concomitant decrying Western values and ethics, the struggle against selfhatred, and a growing ethnic awareness.Keywords: Amiri Baraka, black power, political thought, African-American politics, andconflict